PEMBATALAN KONTRAK SEPIHAK PENGADAAN BARANG/JASA PEMERINTAH TERKAIT PEMENUHAN PRESTASI YANG BELUM TERSELESAIKAN SETELAH BERAKHIRNYA JANGKA WAKTU KONTRAK - Fennieka Kristianto; Fidela Gracia (Problematika Hukum, 2018)
The development within business sectors in Indonesia is growing rapidly, and it is coherent that within business activities the word, as well as the role of contract, cannot be separated. It is due to the fact that the contract itself is one of the most crucial elements among the relationship of business actors in operating their business activities. One of the prominent business sectors in Indonesia is the procurement of goods/services, both by private or Government. This journal will solely focus on the procurement of goods/services by the Government which is the Government of Indonesia. The procurement of Government goods/services is regulated under Presidential Decree No. 16 year 2018 concerning the Procurement of Government goods/services (hereinafter referred to as “Procurement of Government Goods/Services Regulation”). Consequent to the ratification of this Presidential Decree, it has arisen several issues and concern towards the relevant business actors within this field which includes the conformity of the provisions with the principles of contract law in Indonesia along with the question in which unilateral contract termination/cancellation may occur in the interim of the procurement of Government goods/services contract. The research that is done for this journal is through normative legal research. Pursuant to the thorough examination done in this journal, it can be concluded that the rules and regulations relating to the procurement of goods/services are in conformity with the contract principles in Indonesia, and the cancellation/termination of the contract unilaterally cannot be justified legally if the provider fails to complete their performances within the period written and agreed under the contract as the Procurement of Government Goods/Services Regulation permit the extension of the work period.